PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI STATISTIKA SISWA KELAS VIII SMP NEGERI 14 MERANGIN - Rina Sherina; M. Jainuri; Sugeng Riyadi (Pendidikan Matematika | Universitas Merangin, 2024)
The goal of this study is to create a LKPD based on CTL that is valid, practical and effective. This study employed the research and development (R&D) technique.. The characteristics of LKPD based CTL are that it is real (concrete), clarifies a problem, is easy to use, has special characteristics. LKPD based on CTL was validated by 5 experts, 5 expert validators, namely material experts, language experts, media experts, and teacher experts in the field of mathematics at SMP Negeri 14 Merangin. Product validity can be determined from the results of the validation sheet. The results of student interviews and questionnaire responses can be used to assess how useful the product is. Learning outcomes and learning activities can be used to determine effectiveness.The average validation results by material experts was 4.36 in the very valid category, validation results by language experts were 4.70 in the very valid category, validation results by media experts were 4.00 in the very valid category, and validation results by teachers mathematics was 4.60 and the overall validation results were 4.42 in the very valid category. Product practicality obtained a percentage of 77.64% in the practical category. Product effectiveness, in terms of student learning outcomes, obtained a completion percentage of 77.27% in the effective category. Meanwhile, for learning activities, students obtained a percentage of 84.44% in the very active category. The results of research and development show that the CTL-based LKPD created is valid, useful and efficient.